Reviews. Issue 1 (1st August 2009) - Payne, John; León-Solís, Fernando; Labanyi, Jo; Pavia, Carme Ferr; López, Bernat
Catalonia: a cultural history, Michael Eaude (2007) Oxford: Signal Books, 281pp., ISBN 978-1-904955-32-0, Paperback, 12.00The Basque Country: a cultural history, Paddy Woodworth (2007) Oxford: Signal Books, 290 pp., ISBN 978-1-904955-31-3, Paperback, 12.00Analysing Identities in Discourse, Rosana Doln and Jlia Todol (eds) (2008) Amsterdam: John Benjamins Publishing Company, 204 pp., ISBN 978 90 272 2719 5N, Hardback, 105, 00Contemporary Spanish Cinema and Genre, Jay Beck and Vicente Rodrguez Ortega (eds) (2008) Manchester: Manchester University Press, 310pp, ISBN 978-0-7190-7775-3, Hardback, 65.14The Media in Scotland, Neil Blain and David Hutchinson (eds), (2008) Edinburgh: Edinburgh University Press, 286 pp., ISBN 978 0 7486 2800 1, Paperback, 17.99, ISBN 978 0 7486 2799 8, hardback, 52.50La recerca en comunicaci en el Pas Valenci (Research into communication in Valencia), Gmez Mompart, Josep Llus (ed): special issue of Treballs de Comunicaci, no. 22 (June 2007; first edition June 2008) Barcelona: Societat Catalana de Comunicaci, 314 pp., ISBN 1131-5687, paperback, 7, 50 .